Moderately premature infants at Kaiser Permanente Medical Care Program in California are discharged home earlier than their peers in Massachusetts and the United Kingdom. Issue 4 (31st January 2006) - Profit, J; Zupancic, J A F; McCormick, M C; Richardson, D K; Escobar, G J; Tucker, J; Tarnow-Mordi, W; Parry, G
Abstract : Objective: To compare gestational age at discharge between infants born at 30–34 +6 weeks gestational age who were admitted to neonatal intensive care units (NICUs) in California, Massachusetts, and the United Kingdom. Design: Prospective observational cohort study. Setting: Fifty four United Kingdom, five California, and five Massachusetts NICUs. Subjects: A total of 4359 infants who survived to discharge home after admission to an NICU. Main outcome measures: Gestational age at discharge home. Results: The mean (SD) postmenstrual age at discharge of the infants in California, Massachusetts, and the United Kingdom were 35.9 (1.3), 36.3 (1.3), and 36.3 (1.9) weeks respectively (p  =  0.001). Compared with the United Kingdom, adjusted discharge of infants occurred 3.9 (95% confidence interval (CI) 1.4 to 6.5) days earlier in California, and 0.9 (95% CI −1.2 to 3.0) days earlier in Massachusetts. Conclusions: Infants of 30–34 +6 weeks gestation at birth admitted and cared for in hospitals in California have a shorter length of stay than those in the United Kingdom. Certain characteristics of the integrated healthcare approach pursued by the health maintenance organisation of the NICUs in California may foster earlier discharge. The California system may provide opportunities for identifying practices for reducing the length of stay of moderately premature infants.